THE DIFFICULT DOCTRINE OF THE LOVE OF GOD - CARSON, D.A (WHEATON, ILLINOS USA Crossway books, 2000)
The Difficult Doctrine of the Love of God seeks to restore what we have lost. In this treatment of many of the Bible's passages regarding divine love, noted evangelical scholar D. A. Carson not only critiques sentimental ideas such as "God hates the sin but loves the sinner," but provides a compelling perspective on the nature of God and why He loves as He does. Carson blends his discourse with discussion of how God's sovereignty and holiness complete the biblical picture of who He is and how He loves.